Interferon-induced Protein-44 and Interferon-induced Protein 44-like restrict replication of Respiratory Syncytial Virus - Tregoning,J; Busse,D; Kaforou,M; Levin,M; Herberg,J; Kellam,P; Bassano,I (Journal of Virology, 2020)
Cellular intrinsic immunity, mediated by the expression of an array of interferon-stimulated antiviral genes, is a vital part of host defence. We have previously used a bioinformatic screen to identify two interferon stimulated genes (ISG) with poorly characterised function, Interferon-induced protein 44 (IFI44) and interferon-induced protein 44-like (IFI44L), as potentially being important in Respiratory Syncytial Virus (RSV) infection. Using overexpression systems, CRISPR-Cas9-mediated knockout, and a knockout mouse model we investigated the antiviral capability of these genes in the control of RSV replication. Over-expression of IFI44 or IFI44L was sufficient to restrict RSV infection at an early time post infection. Knocking out these genes in mammalian airway epithelial cells increased levels of infection. Both genes express antiproliferative factors that have no effect on RSV attachment but reduce RSV replication in a minigenome assay. The loss of Ifi44 was associated with a more severe infection phenotype in a mouse model of infection. These studies demonstrate a function for IFI44 and IFI44L in controlling RSV infection.